Morphology and composition of oxidized InAs nanowires studied by combined Raman spectroscopy and transmission electron microscopy. (20th June 2016) - Tanta, Rawa; Kanne, Thomas; Amaduzzi, Francesca; Liao, Zhiyu; Madsen, Morten H; Alarcón-Lladó, Esther; Krogstrup, Peter; Johnson, Erik; Morral, Anna Fontcuberta i; Vosch, Tom; Nygård, Jesper; Jespersen, Thomas S
Abstract: Any device exposed to ambient conditions will be prone to oxidation. This may be of particular importance for semiconductor nanowires because of the high surface-to-volume ratio and only little is known about the consequences of oxidation for these systems. Here, we study the properties of indium arsenide nanowires which were locally oxidized using a focused laser beam. Polarization dependent micro-Raman measurements confirmed the presence of crystalline arsenic, and transmission electron microscopy diffraction showed the presence of indium oxide. The surface dependence of the oxidation was investigated in branched nanowires grown along the [ 0001 ] and [ 01 1 ̄ 0 ] wurtzite crystal directions exhibiting different surface facets. The oxidation did not occur at the [ 01 1 ̄ 0 ] direction. The origin of this selectivity is discussed in terms transition state kinetics of the free surfaces of the different crystal families of the facets and numerical simulations of the laser induced heating.